2016
DOI: 10.1002/2016ja022650
|View full text |Cite
|
Sign up to set email alerts
|

Two types of whistler waves in the hall reconnection region

Abstract: Whistler waves are believed to play an important role during magnetic reconnection. Here we report the near‐simultaneous occurrence of two types of the whistler‐mode waves in the magnetotail Hall reconnection region. The first type is observed in the magnetic pileup region of downstream and propagates away to downstream along the field lines and is possibly generated by the electron temperature anisotropy at the magnetic equator. The second type, propagating toward the X line, is found around the separatrix re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 49 publications
5
76
2
Order By: Relevance
“…In Figure 4f, only the PSDs at θ = 0°(black), θ = 90°(red), and θ = 180°(blue) are shown, while in Figure 4g, the PSDs at all pitch angles are presented. In this event, we notice that the whistlers were propagating outward from the EDR, inconsistent with those suggested in streaming-instability scenario [Huang et al, 2016]. In previous studies, streaming instabilities [Divin et al, 2012] and the associated electron holes [Goldman et al, 2014] at separatrices and the perpendicular anisotropy of suprathermal electrons [e.g., Khotyaintsev et al, 2011;Fu et al, 2014] have been suggested as two possible mechanisms responsible for the generation of whistlers.…”
Section: Electron Distribution and Wave Generationcontrasting
confidence: 68%
See 1 more Smart Citation
“…In Figure 4f, only the PSDs at θ = 0°(black), θ = 90°(red), and θ = 180°(blue) are shown, while in Figure 4g, the PSDs at all pitch angles are presented. In this event, we notice that the whistlers were propagating outward from the EDR, inconsistent with those suggested in streaming-instability scenario [Huang et al, 2016]. In previous studies, streaming instabilities [Divin et al, 2012] and the associated electron holes [Goldman et al, 2014] at separatrices and the perpendicular anisotropy of suprathermal electrons [e.g., Khotyaintsev et al, 2011;Fu et al, 2014] have been suggested as two possible mechanisms responsible for the generation of whistlers.…”
Section: Electron Distribution and Wave Generationcontrasting
confidence: 68%
“…For instance, Deng and Matsumoto [2001] reported a good mediation of reconnection rate by whistlers at the Earth's magnetopause, using the Geotail data; Wei et al [2007] observed whistlers prior to reconnection and enhancement of whistlers during reconnection in the Earth's magnetotail, using the Cluster data; Huang et al [2016] presented two types of whistlers during Hall magnetic reconnection, using the Cluster data; Graham et al [2016], Le Contel et al [2016a], and Wilder et al [2016] observed strong whistler emissions in the separatrix region, using the Magnetospheric Multiscale (MMS) data; Khotyaintsev et al [2016] reported whistlers in the outflow region, using MMS data. For instance, Deng and Matsumoto [2001] reported a good mediation of reconnection rate by whistlers at the Earth's magnetopause, using the Geotail data; Wei et al [2007] observed whistlers prior to reconnection and enhancement of whistlers during reconnection in the Earth's magnetotail, using the Cluster data; Huang et al [2016] presented two types of whistlers during Hall magnetic reconnection, using the Cluster data; Graham et al [2016], Le Contel et al [2016a], and Wilder et al [2016] observed strong whistler emissions in the separatrix region, using the Magnetospheric Multiscale (MMS) data; Khotyaintsev et al [2016] reported whistlers in the outflow region, using MMS data.…”
Section: Introductionmentioning
confidence: 99%
“…The present model can explain the bursty nature of whistler emissions as observed in the Earth's magnetosphere (e.g., Deng and Matsumoto, 2001;Wei et al, 2007;Tang et al, 2013;Graham et al, 2016;Huang et al, 2016;Zhao et al, 2016). The key processes to generate the whistlers are intense perpendicular heating of the electrons in association with plasmoid collision and the subsequent compression of the ambient magnetic field.…”
Section: Discussionmentioning
confidence: 97%
“…Whistler waves are fundamental plasma waves frequently observed in space in association with transient phenomena, such as collisionless shocks (e.g., Olson et al, 1969;Rodriguez and Gurnett, 1975;Lengyel-Frey et al, 1996;Zhang et al, 1999;Hull et al, 2012) and magnetic reconnection (e.g., Deng and Matsumoto, 2001;Wei et al, 2007;Tang et al, 2013;Graham et al, 2016;Huang et al, 2016;Zhao et al, 2016;Uchino et al, 2017). The waves have a righthand polarization with respect to the ambient magnetic field, so they can couple with the electrons through the cyclotron resonance and give rise to pitch-angle scattering and parallel acceleration (e.g., Kennel and Petschek, 1966;Gary and Wang, 1996;Schreiner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a finite amplitude single electrostatic wave can be excited by a small cold beam 10,11 . Whistler waves can also be excited by an electron beam in a number of space plasma settings 1,[12][13][14] . Some electrostatic structures, such as double layers and electron holes, seems to be generated by current-carrying electron beams in the presence of density inhomogeneities 15 .…”
Section: Introductionmentioning
confidence: 99%